2014
DOI: 10.1074/jbc.m113.515080
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Methylenedioxy-β-nitrostyrene Inhibits NLRP3 Inflammasome Activation by Blocking Assembly of the Inflammasome

Abstract: Background:The NLRP3 inflammasome is a critical component of the innate immune system, and its malfunction contributes to the pathogenesis of inflammatory diseases. Results: Nitrostyrene specifically inhibits NLRP3 activation. Conclusion: Nitrostyrene blocks the assembly of NLRP3 inflammasome by inhibiting NLRP3 ATPase activity. Significance: We identify a novel chemical probe for studying the molecular mechanism of NLRP3 inflammasome activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
197
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(211 citation statements)
references
References 47 publications
5
197
2
2
Order By: Relevance
“…NS, not significant. after LPS priming followed by silica stimulation, whereas the opposite behavior was observed for IL-1␤ secretion (47). Leptin also increased IL-18 secretion by human monocytes, while the same effect was not observed for IL-1␤ secretion (48).…”
Section: Discussionmentioning
confidence: 82%
“…NS, not significant. after LPS priming followed by silica stimulation, whereas the opposite behavior was observed for IL-1␤ secretion (47). Leptin also increased IL-18 secretion by human monocytes, while the same effect was not observed for IL-1␤ secretion (48).…”
Section: Discussionmentioning
confidence: 82%
“…127 In the screening of a kinase inhibitor library in another recent study, 3,4-methylenedioxy-b-nitrostyrene (MNS) was identified by the prevention of NLRP3-mediated ASC speck formation through targeting NLRP3 or NLRP3-associated complexes. 128 It is also noted that caspase-1, in spite of its essential role in the assembly of NLRP3 inflammasome, is found to play a critical regulatory role in house dust mite-induced allergic lung inflammation through downregulation of IL-33. 129 Recent studies have identified a key role of autophagy in activation of the NLRP3 inflammasome.…”
Section: Negative Regulation Of Nlrp3 Inflammasome Complex Activationmentioning
confidence: 99%
“…Specific mono-and di-substitutions on the aromatic ring of β-nitrostyrene tended to increase the anti-platelet activity and decrease the cytotoxic activity [17]. 3,4-Methylenedioxy-β-nitrostyrene (MNS) blocks the assembly of NLRP3 inflammasome by the inhibition of NLRP3 ATPase activity [18,19]. The nitrovinyl group is essential for the inhibitory activity of MNS.…”
Section: Mechanism Of Antibacterial Activitymentioning
confidence: 99%